(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Geotechnical coal mining integrates geological, geomechanical, and engineering principles to ensure the safe and efficient extraction of coal resources. As mining operations progress to deeper and more structurally complex deposits, understanding the mechanical behavior of rock masses, stress redistribution, and ground stability becomes increasingly critical. This study examines key geotechnical factors influencing coal mine design, including rock mass characterization, slope and roof stability, subsidence prediction, groundwater control, and the application of monitoring systems for early hazard detection. Modern methods such as numerical modeling, geophysical exploration, and real-time geotechnical monitoring are highlighted as essential tools for improving mine planning and preventing failures such as roof collapses, gas outbursts, and landslides. The research emphasizes the importance of integrating geotechnical risk assessment into mining operations to enhance worker safety, optimize resource extraction, and reduce environmental impacts. Findings indicate that geotechnically informed decision-making significantly improves mine stability and sustainability, especially in regions with complex geological conditions.